Dick King-Smith's book of pets Five classic tales from the Master of Animal adventure - King-Smith,Dick; Illustrator; John Eastwood (London, Puffin, 2017)
In this collection of stories, you will meet a guineapig that can do clever tricks, the Queen's favorite Corgi pup, a secret mouse hiding in a treehouse, a chick that wants to be a duck and you'll learn how to look after all kinds of pets! A delightful anthology from the king of animal stories Dick King-Smith, featuring a never-before-published story
A2 fiction shelf
Keywords: English fiction story